Ecological Justice in the Framework of Pancasila: Problems and Challenges - Nurhuda, Ikhsan; Baiquni, Muhammad Iqbal (Indonesian Journal of Pancasila and Global Constitutionalism, 2024)
This paper examines the concept of ecological justice within the framework of Pancasila, the philosophical foundation of the Indonesian state. While Pancasila emphasizes socio-cultural harmony and collective welfare, its application to ecological issues poses significant challenges. This analysis delves into the complexities of achieving ecological justice within the Pancasila framework, identifying key problems and challenges. Beginning with an exploration of Pancasila's core principles, the paper highlights its emphasis on social justice, democracy, and collective responsibility. It then discusses the intersection between Pancasila and environmental concerns, emphasizing the need for ecological justice to address issues such as environmental degradation, biodiversity loss, and climate change. Drawing on case studies and theoretical perspectives, the paper identifies several challenges in applying Pancasila to ecological justice. These challenges include reconciling traditional values with modern environmental imperatives, balancing economic development with environmental sustainability, and addressing power disparities in environmental decision-making. Furthermore, the paper examines the role of governance structures, policy frameworks, and civil society in promoting ecological justice within the Pancasila framework. It discusses potential pathways for integrating environmental considerations into Pancasila-based policies and practices. Through this analysis, the paper contributes to the discourse on ecological justice by exploring its intersection with indigenous philosophical frameworks like Pancasila. It underscores the importance of incorporating environmental concerns into Pancasila-based governance to ensure a more sustainable and equitable future for Indonesia and beyond.